Anemia pada Wanita Hamil - R. Soeprono, R. Soeprono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
Among complications affecting the pregnant woman, anemia is more frequently encountered than is usually realized, consequently becoming not infrequently overlooked in diagnosis, prognosis and therapy.Preexistent conditions as low socio-economic status, under or malnutrition, multiparity with short intervals, chronic occult bleeding or evident hemorrhages associated with previous deliveries or menstruation, are, with inadequate antenatal care, the most pertinent factors to deal with in terms of prevention and treatment. Since 95% of pregnancy anemias are iron deficiency anemias because of basically avoidable conditions, this specific iron deficiency problem deserves the most serious attention. Although of no marked consequence when of mild gradation, in moderate and severe cases all anemias of pregnancy Ã¢â¬â irrespective of etiology Ã¢â¬â tend to exert deleterious effects on the reproductive process, directly or indirectly.Key Words: anemia in pregnancy iron deficiency nutrition - pregnancy spacing -hematologic index